2015
DOI: 10.1007/s00704-015-1677-6
|View full text |Cite
|
Sign up to set email alerts
|

Complexity analysis of the air temperature and the precipitation time series in Serbia

Abstract: In this paper, we have analyzed the time series of daily values for three meteorological elements, two continuous and a discontinuous one, i.e., the maximum and minimum air temperature and the precipitation. The analysis was done based on the observations from seven stations in Serbia from the period 1951-2010. The main aim of this paper was to quantify the complexity of the annual values for the mentioned time series and to calculate the rate of its change. For that purpose, we have used the sample entropy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The annual quantity of rainfall is often insufficient, and droughts are evident in eastern and south-eastern parts of Serbia [28]. Scenarios where the monthly quantity of precipitation falls in only a few days of the month are expected to become more frequent, which will lead to more extreme weather events such as floods and droughts [29]. Serbia has two peaks in its fire season [30].…”
Section: Study Areamentioning
confidence: 99%
“…The annual quantity of rainfall is often insufficient, and droughts are evident in eastern and south-eastern parts of Serbia [28]. Scenarios where the monthly quantity of precipitation falls in only a few days of the month are expected to become more frequent, which will lead to more extreme weather events such as floods and droughts [29]. Serbia has two peaks in its fire season [30].…”
Section: Study Areamentioning
confidence: 99%
“…In the meanwhile, in the theory of nonlinear dynamical systems an interesting and easily applicable tool known as complexity measure or Kolmogorov complexity (KC) [19,20] has been proposed. Today it is closely related to the information theory [19][20][21][22], and applied in many other fields such as hydrology [23], climatology [24,25], etc. The complexity measure represents a useful quantity, which characterizes spatiotemporal patterns and provides fine measure of order, i.e., periodic motion and chaotic behavior.…”
mentioning
confidence: 99%
“…Considering that a signal with a high value of α 0 , a wide range W of fractal exponents (higher degree of multifractality), and a right-skewed shape (r > 0) may be considered more complex than those with opposite characteristics [52], the observed changes of multifractal parameters (Figure 4) indicated that in the second period overall complexity of temperature series increased in northern part of country, and decreased in southern part. Mimić et al [57] analyzed the complexity of daily maximum and minimum temperature and daily precipitation from seven station on Serbia (recorded during the period 1951-2010) using information theory measures Kolmogorov complexity and Sample entropy. They found that for all stations both measures (calculated for 1year periods) exhibit positive trend for maximum temperature indicating the increase in complexity.…”
Section: Multifractal Analysismentioning
confidence: 99%